After Whom is Herschel Island Named? - Burn, C.R. (ARCTIC, 2009)
Herschel Island (Qikiqtaruk) is a seasonally inhabited island off the western Arctic coast of Canada. It was designated as a Yukon territorial park under the Inuvialuit Final Agreement (1987) in recognition of its physical and cultural significance. The island was named by Captain John Franklin of the Royal Navy on 15 July 1826, during his second voyage of Arctic exploration. Unlike entries for other features named by Franklin along this coast, the journal record of this event does not indicate the specific person after whom he named the island. Franklin’s journal and his published account state only that he wished to honour the name Herschel, borne most prominently by Sir William Herschel, who discovered the planet Uranus, Sir William’s sister Caroline Herschel, who discovered eight comets, and Sir William’s son Sir John Herschel, the brilliant polymath; in other words, he wished to honour this preeminent late Georgian scientific family. L’île Herschel (Qikiqtaruk) est une île de la côte Ouest de l’Arctique du Canada qui est habitée selon les saisons. Elle a été désignée en tant que parc territorial du Yukon en vertu de la Convention définitive des Inuvialuit (1987) en raison de son importance physique et culturelle. Cette île a été nommée par le commandant John Franklin de la Marine royale le 15 juillet 1826 dans le cadre de sa deuxième expédition d’exploration de l’Arctique. Contrairement aux autres endroits ayant été nommés par Franklin tout au long de cette côte, le journal de bord ne mentionne nullement en l’honneur de quelle personne l’île a été nommée. Le journal de Franklin de même que son récit publié indiquent seulement qu’il voulait rendre hommage au nom Herschel, porté notamment par Sir William Herschel, qui a découvert la planète Uranus, par la soeur de Sir William, Caroline Herschel, qui a découvert huit comètes et par le fils de Sir William, Sir John Herschel, ce brillant homme. Autrement dit, il voulait honorer cette famille scientifique prééminente de la fin de l’époque géorgienne.